A selection of fifty type specimens from the collection of Tobias Frere-Jones. - Frere-Jones, Tobias, 1970-; Stössinger, Nina. (New York : Princeton Architectural Press, 2017)
Curated by renowned type designer Tobias Frere-Jones, this collection features fifty postcards drawn from his extraordinary personal collection of type specimen books. These stunning cards feature typography from four countries: the United States, Great Britain, France, and Germany.
Item consists of a single-fold introductory pamphlet and fifty postcards separated into geographic categories by four thumb tabs, all enclosed in a box.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Type and type-founding -- United States -- Facsimiles; Type and type-founding -- Great Britain -- Facsimiles; Type and type-founding -- France -- Facsimiles; Type and type-founding -- Germany -- Facsimiles; Printing -- Specimens -- Facsimiles; Printing; Type and type-founding.; France; Germany; Great Britain; United States; Type specimens; Facsimiles; Specimens